Manajemen Perencanaan Program Baca Tulis Al-Qur'an Di TPA Al Hijrah Kecamatan Gandus Kota Palembang - Nur Istikomah; Ade Akhmad Saputra (CV. ITTC INDONESIA, 2026)
This study aims to describe and analyze the planning management of the Al-Qur’an Reading and Writing (BTA) program at Al-Hijrah Gandus TPA in Palembang City. The background of this study is the importance of planning in supporting the success of Al-Qur’an learning to improve students’ ability to read and write the Qur’an. The focus of the study includes analysis of program needs, formulation of objectives, preparation of programs and schedules, preparation of resources (ustadzah, facilities, and funds), and the effectiveness of BTA program planning. This study uses a qualitative approach with a descriptive design. Data were collected through interviews, observations, and documentation involving ustadzah as key informants in the planning and implementation process. Data analysis was conducted using the Miles, Huberman, and Saldaña model, including data reduction, data display, and conclusion drawing and verification. The results show that the planning of the BTA program has been implemented systematically through needs identification, objective setting, structured program and schedule preparation, and adequate resource allocation. The planning process is considered effective, as the program runs according to schedule and contributes to the improvement of students’ Qur’an reading and writing abilities.